SINERGI PERGURUAN TINGGI, PERANGKAT DESA DAN LEMBAGA SOSIAL UNTUK MEWUJUDKAN DESA WISATA PETIK JERUK SELOREJO - yupono bagyo; amir kusnanto; tachjuddin tachjuddin; sugeng hariadi; siwi dyah ratnasari; dwi daenasty decasari (Universitas Kadiri, 2017)
The majority of Selorejo villagers are farmers of citrus crops. Selorejo orange product is famous and has 12 kinds of oranges. Regent of Malang, Mr. H. Rendra Krisna expects Selorejo village to be a pilot village of citrus picking tour in Malang regency.The problems of Selorejo Village, Malang, are: a) people are still not ready to receive tourist visit from both domestic and foreign; b) Spatial village is not yet tidy including layout of bus parking and tour vehicle; c) The need to centralize the sale of citrus and other processed citrus products; d) Assisting the empowerment of villagers with more rooms for tourists; and e) lack of promotion.Solutions are offered 1-year IbDM Program that is a) Entrepreneurship Training, GAPOKTAN, PKK, Karang Taruna / Tour manager; b) Map of Citrus Tourist Sites; c) Making citrus kiosks and village superior products; d) Clean the sewer from plastic waste; e) Website Creation; f) Making of drainage in citrus hut; and g) Making of citrus hut.The method of implementation in achieving the specific objectives of the IbDM Program is in accordance with the needs of the villagers of Selorejo, the Implementing Team conducts training to GAPOKTA, PKK, Tour Manager / Karang Taruna, including entrepreneurship training, marketing, accounting. In addition, the team implements the implementation of science and technology in the form of website creation, and improvement of tourism infrastructure facilities.Achievements of 1st year IbDM program activities are: a) Prime Service Training, Entrepreneurship and Accounting for GAPOKTAN, PKK, Tour Manager / Karang Taruna; b) Map of Citrus Tourist Sites; c) Create a Gazebo for the marketing of the Village's Featured Products; d) Website Creation; e) Making drains in citrus huts; and f) Making of citrus hut. So 100% of 1 year IbDM program has been implemented.